Contract theory: Impact on biopharmaceutical alliance structure and performance - TANERI, Niyazi (Institutional Knowledge at Singapore Management University, 2017)
Alliances for new product development have been studied extensively in the operations management literature. Alliances between an innovator and a partner create value by utilizing their complementary capabilities. In this paper, we seek to understand what drives the alliance structure: the choice between collaborative alliances where the parties exert joint efforts and sequential alliances where, for the most part, the partner takes over going forward. Our analysis of a data set of over 2,000 biopharmaceutical alliances reveals our main finding: a key role of operational choices is to address contract theoretic concerns faced by an alliance.We also find that aligning the choice with predictions based on contract theory has consequences for performance. Therefore, our analysis not only has descriptive power about the drivers of alliance choice, but also provides valuable insight into the performance and eventual fate of alliances formed.